Transition Services in Order to Prepare the Financial Independence of Students with Mild Intellectual Disabilities in Purnama Asih Special Needs School Bandung - Asep Rudi Irawan; Tjutju Soendari; Mimin Tjasmini (Journal of ICSAR, 2019)
This research aims to describe the implementation of transition services to prepare students with mild intellectual disabilities to be financially independent in Special Needs School Bandung. This research was conducted using a qualitative approach with case study. The research subject was the teachers, teacher coordinators, principals, two parents, and two students with mild intellectual disabilities (ID). Data were collected using observation, interviews, and documentation and analyzed by data reduction, display, and verification processes. The results of this research described the transition services provided by the school to meet the needs of the students which are 1) self-determination; 2) access to workplace; 3) mutual understanding; 4) knowledge, competence and skills to work. This research concluded that the implementation of transition services in SLBC in Bandung has not been optimal to prepare students to be financially independent.